La gestión de Álvarez de Arenales. Presencia del rivadianismo en Salta (1824-1827) - Di Pasquale, Mariano (Revista Complutense de Historia de América, 2010)
This article studies the power-based relationships between the elites of Salta and Buenos Aires, represented by Álvarez de Arenales and Bernardino Rivadavia, respectively, between 1824 and 1827. It analyses, from an integral perspective, the alternatives to the political process articulated by these elite sectors of the La Plata region. The existence of the accommodation of powers is studied, as well as the application of similar reformist policies and their possible foundations in both scenarios. The article also points to the fact that the elite of Salta sought the support of the government of Buenos Aires, in order to obtain political benefits and financial backing, as they faced the risk of possible territorial disintegration, brought on by the War of Independence. In this context, the article examines the political interests that played out during the National Constituent Congress of 1824-1827 and the problems surrounding the issue of the Tarija territory, nort of Salta Province.